2022
DOI: 10.3390/coatings12030399
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Surface Conditioning Techniques on the Bonding between Resin Cement & Ceramic

Abstract: Surface etching before cementation is a vital step that determines the clinical performance of ceramic restorations. Etching alters surface topography that contributes effective bonding between ceramic restoration and resin cement. This study aimed to compare etching techniques to determine the most effective etching method contributing the highest bond strength that helps in improving dental implants. Materials and methods: sixty discs of feldspathic ceramic measuring 10 mm diameter and 4 mm thickness were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…6,7 Hence, the study was conducted to determine the combined effect of hydrofluoric acid and phosphoric acid on the surface of lithium-disilicate veneers. [8][9][10] In this study, the heat-pressed veneers were milled and sintered before bonding the veneers to the tooth structure. The total number of 22 samples were divided into two groups: 11 samples in group A and 11 samples in group B.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Hence, the study was conducted to determine the combined effect of hydrofluoric acid and phosphoric acid on the surface of lithium-disilicate veneers. [8][9][10] In this study, the heat-pressed veneers were milled and sintered before bonding the veneers to the tooth structure. The total number of 22 samples were divided into two groups: 11 samples in group A and 11 samples in group B.…”
Section: Discussionmentioning
confidence: 99%
“…Treating the ceramic surface to increase surface roughness is a key to the success and prognosis of the bond strength between ceramic and resin luting cement, which may increase the bond strength between the ceramic surface and the resin cement [24][25][26]. The recently introduced fully crystallized glass ceramic, ZLS, which can be cemented directly after milling with simple polishing or heating for 10 min, has also helped to decrease treatment time.…”
Section: Discussionmentioning
confidence: 99%
“…Laser irradiation is considered a modern method for treating ceramic surfaces. Lasers concentrate and focus an enormous amount of energy on a small target area, which causes micromorphological physical changes by absorbing the energy [15]. Sevmez and Yilmaz demonstrated that different surface treatments have different effects on surface roughness and bond strength in ZLS, but also that higher surface roughness does not always lead to higher bond strength [14].…”
Section: Introductionmentioning
confidence: 99%